Plio‐Pleistocene Hemispheric (A)Symmetries in the Northern and Southern Hemisphere Midlatitudes. Issue 3 (17th March 2020) - Peterson, L. C.; Lawrence, K. T.; Herbert, T. D.; Caballero‐Gill, R.; Wilson, J.; Huska, K.; Miller, H.; Kelly, C.; Seidenstein, J.; Hovey, D.; Holte, L.
Abstract: The transition from the warm, stable climate of the Pliocene to the progressively colder glaciations of the Pleistocene, as well as the climate system's evolving response to stationary orbital forcing over the Pleistocene, beg important questions about fundamental climate processes relevant to understanding the impacts of modern anthropogenic forcing of the Earth's energy budget. Here, we gain insight into the evolution of Plio‐Pleistocene climate by generating an alkenone‐derived, orbitally resolved sea surface temperature (SST) record from Ocean Drilling Program Site 1125 in the southwest Pacific. We compare our data set to midlatitude and equatorial SST records and to the benthic ∂ 18 O signal in order to evaluate similarities and differences in climate response between the hemispheres and across latitudes over the Plio‐Pleistocene. Secular trends indicate first‐order symmetry between the Northern and Southern Hemispheres in the magnitude of mean, glacial, and interglacial cooling. However, the tight coupling that is observed on both secular and orbital timescales between Northern Hemisphere, high latitude, and tropical upwelling climate throughout the last 4 Ma does not extend to Southern Hemisphere climate records as Northern Hemisphere glaciation intensifies in the late Pliocene. The 41‐kyr signal remains weak at Site 1125 across the late Pliocene transition but strengthens in conjunction with a major increase in global climate system sensitivity to obliquity forcing beginning around 1.8 Ma. Our analysis points to regionally varied responses across the late Pliocene transition and the emergence of a global feedback mechanism and strengthened obliquity‐band climate sensitivity just prior to the mid‐Pleistocene transition. Key Points: We compare temperature change in the southwest Pacific Ocean to climate records from other regions to evaluate climate evolution over the last 4.2 million years Many aspects of midlatitude Southern Hemisphere climate appear decoupled from the Northern Hemisphere and tropics over the late Pliocene transition Climate sensitivity to obliquity rises in the southwest Pacific Ocean and across the climate system beginning ~1.8 Ma, preceding the mid‐Pleistocene transition